Tanggung Jawab Perdata Pihak Pengusaha Gelodongan Emas Secara Ilegal Terhadap Pencemaran Limbah Merkuridi Desa Lalar Liang : (Studi Kecamatan Taliwang Kabupaten Sumbawa Barat) - Titik Mill Enia Zamantha; Muhammad Irfan (Fakultas Hukum Universitas Mataram, 2022)
This study aims to analyze the civil liability of gold bar entrepreneurs for environmental pollution due to mercury waste and the efforts made by local governments to mitigate and protect the environment due to mining activities. The type of research used is empirical normative legal research. The results of this study indicate that gold processing activities in Lalar Liang Village do not have a permit and are carried out illegally as well as efforts made by local governments with preventive and repressive efforts, namely issuing regional regulations, socialization, stabilization, and environmental mitigation. pollution due to illegal mining, namely by changing jobs or professions, reducing the use of mercury. However, this activity is still carried out because it helps the community's economy so that they can continue their lives.